ANALISIS LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PADA PT MAYORAN INDAH,Tbk YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sitorus, Fauziyah; Siregar, Liper; Inrawan, Ady; Nainggolan, Christine (SULTANIST: Jurnal Manajemen dan Keuangan, 2019)
The purpose of this research are : 1. Know the description of the company,s financial performance at PT Mayora Indah, Tbk. 2. To find out what factors caused Mottled financial performance at PT Mayora Indah, Tbk tend to increase. The research was conducted using qualitative, descriptive methods of analysis, methods of trend and inductive methods. The research of the data is qualitative and quantitative data. The data of this research is used secondary data. Data collection is used by the method of documentation.            The results of this research can be summed up as follows: 1. Trend quick ratio has increased. Trend in the Debt to asset Ratio has increased. Total Assets Turn over trend has increased. The trend of Return On Assets (ROA), Return On Equity (ROE), the Net Profit Margin (NPM) experienced an increase in the company's financial performance so that it can be said better. 2. The factors that lead to good performance is the business accounts receivable, short term loans, increased sales and inventory.            The results of the analysis suggest that PT Mayora Indah, Tbk We recommend you be cautious in doing short term loans. In addition the company should improve the effectiveness of the management of inventory. Should the company optimizes the management of accounts receivable in order to collect the accounts receivable business to the company. We recommend that you keep the company sales activity is stable so that the company obtained more optimal net profit margin.